Structural design and thermal performance simulation of shade roof of double-slope greenhouse for mushroom-vegetable cultivation - Ma, Yunfei; Li, Xinxing; Fu, Zetian; Zhang, Lingxian (International Journal of Agricultural and Biological Engineering, 2019)
A new type of roof structure was developed for the shade room in a double-slope greenhouse used for mushroom-vegetable planting. A simulation model was developed to evaluate the thermal performance of the new roof with an insulation thickness of 0.12 m in Beijing, China. The results showed that (1) the indoor air temperature of the shade room with the newly implemented shade roof was 2.7°C-4.9°C higher than that of an ordinary shade room during the winter months; (2) The indoor air temperature of the solar room adjacent to the shade room with the new roof was higher than that of the ordinary solar room and the minimum indoor air temperature of the solar room was increased 1.9°C at winter night; (3) the indoor temperature of the shade room with the new roof design was 2°C-4°C lower than that of the ordinary shade room during the summer months; (4) Under factory production conditions, which were conducted in a controlled environment to promote the annual growth of the edible fungus, the heating energy consumption of the shade room after the implementation of the new roof structure was reduced by 69.3%, the amounted to total energy savings of 61.3% per year. The new roof structure provided a significant improvement in the thermal environment compared to an ordinary shade room, improved the vegetable growth in the winter, and also significantly reduced the energy consumption and production costs. Keywords: double-slope greenhouse, roof structure design, thermal performance simulation, mushroom-vegetable planting DOI: 10.25165/j.ijabe.20191203.4852 Citation: Ma Y F, Li X X, Fu Z T, Zhang L X. Structural design and thermal performance simulation of shade roof of double-slope greenhouse for mushroom-vegetable cultivation. Int J Agric & Biol Eng, 2019; 12(3): 126–133.